Reel eaudiobook - Ryan, Kennedy (Hollywood Renaissance, 2024)
A Broadway actress has a chance at stardom when cast by a major Hollywood director, but the role of her dreams may cost her the love of a lifetime in this epic novel from "one of the finest romance writers of our age." ( Entertainment Weekly ) For months I stood in the wings, an understudy waiting for my time to shine. I never imagined he would be in the audience that night. Canon Holt. Famous film director. Talented. Fine. Before I could catch my breath, everything changed. I went from backstage Broadway to center stage Hollywood. From being unknown, to my name, Neevah Saint, on everyone's lips when Canon casts me in a star-studded Harlem Renaissance biopic. But stars shine brightest in the dead of night. Forbidden attraction, scandal and circumstances beyond my control jeopardize my dream. Could this one shot—the role and love of a lifetime—cost me everything? This beautiful new edition includes a never-before-published bonus epilogue! ·Entertainment Weekly Best Romances of the Year ·Washington Post Best Romances of the Year ·BookBub's Highest Rated Books of the Year ·LA Times 50 Best Hollywood Books of All Time